Holy Land Archaeology: Where the Past Meets the Present - Meyers, Eric M.; Meyers, Carol (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
This paper discusses the ways the archaeological search for the past can be affected by the situation in an archaeologist’s present. This is especially true for projects in the “Holy Land,” where religious and political issues often play a role in site selection and inthe intepretations of finds. Excavations of five sites (BethAlpha, Hazor, Masada, Jerusalem, and Sepphoris) are examined as examples.